Life transition stages of family caregivers for patients with chronic illness: A grounded theory study - Md Khalid, Norfaezah; Sajali, Nurul Salwa; Razali, Asbah (Belitung Nursing Journal, 2025)
Background: Family caregivers play a crucial role in providing continuous support to individuals with chronic illnesses. Their responsibilities extend beyond the well-being of patients, influencing both patient health outcomes and their own. Caregiving entails significant responsibilities and sacrifices, requiring caregivers to navigate evolving roles and care needs over time. Existing literature highlights the emotional and psychological challenges faced by caregivers, including role transitions and stress. However, most studies focus on caregiving experiences rather than the specific transitional phases caregivers undergo after assuming their responsibilities. Objective: This study aimed to explore the transitional phases experienced by caregivers of chronically ill patients using an inductive approach, specifically grounded theory methodology. Methods: This study employed a grounded theory (GT) approach involving 33 participants, including 24 caregivers and nine professional helpers. Data collection and analysis were carried out between April 2022 and January 2024. Participants were recruited through snowball sampling based on predetermined criteria. Data were collected using semi-structured interviews and memos and analyzed using NVivo 12 software. Several measures were undertaken to ensure the validity and reliability of the data. Results: Findings yielded five stages of life transition, namely, (1) confusion, (2) conflict, (3) consideration, (4) adjustment, and (5) acceptance. Conclusion: This study contributes to the literature by providing new insight into the life transition phases experienced by family caregivers. It offers meaningful implications for nursing practice, particularly in providing holistic support to family caregivers of individuals with chronic illness. It helps nurses to design more targeted, phase-specific interventions that focus on caregivers’ psychosocial needs at each phase. The final model provides a beneficial premise for the development of clinical guidelines and support frameworks that are more responsive to the real experiences of caregivers.